„Nem ölhetik meg jobban a magyar embert!”: Tompa Mihály és az 1851-es dohányrendelet - Patonai, Anikó Ágnes (Studia Litteraria, 2021)
Tobacco products were extremely widespread in Hungary, cultivation and trade functioned as a key sector of the economy, and they also reflected the complex and contradictory relationship between the imperial government and the Orders. Like many of his compatriots, Mihály Tompa used self-grown tobacco, which formed a significant part of his farming, so he was also directly affected by the tobacco monopoly introduced in 1851. Based on the poet’s correspondence, the study seeks to present this involvement and to map how it all related to Tompa’s literary activity.